2006
DOI: 10.1038/sj.jhh.1002015
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type-I degradation is related to arterial stiffness in hypertensive and normotensive subjects

Abstract: Although arterial stiffness is an independent cardiovascular risk factor associated with both aging and hypertension, relatively little is known regarding the structural changes in the vessel wall that occur with vessel stiffening. We determined if collagen type-I metabolism is related to arterial stiffening in both hypertensive and normotensive subjects. Arterial stiffness was assessed by aortic pulse wave velocity (PWV) and augmentation index (AIx) in 46 subjects (48.772 years, 32 hypertensives) and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 33 publications
7
68
3
1
Order By: Relevance
“…53 Other authors have reported an inverse association between arterial stiffness and plasma MMP-1 in hypertensive patients. 54 Although no cardiac parameters were included in a multiple regression analysis to assess whether they influenced the correlations between arterial stiffness and serum biomarkers, these observations suggest that in arterial hypertension, alterations in these molecules may reflect disturbances of collagen metabolism that occur not just at the myocardial but also at the arterial wall level.…”
Section: Aspects Related To the Presence Of Comorbiditiesmentioning
confidence: 99%
“…53 Other authors have reported an inverse association between arterial stiffness and plasma MMP-1 in hypertensive patients. 54 Although no cardiac parameters were included in a multiple regression analysis to assess whether they influenced the correlations between arterial stiffness and serum biomarkers, these observations suggest that in arterial hypertension, alterations in these molecules may reflect disturbances of collagen metabolism that occur not just at the myocardial but also at the arterial wall level.…”
Section: Aspects Related To the Presence Of Comorbiditiesmentioning
confidence: 99%
“…19 We have shown previously a strong association between aortic stiffness and collagen turnover in hypertensive patients. 20 After the initial degradation by collagenases (MMP-1, MMP-8, MMP-13) and elastinase (MMP-7), further degradation of ECM basement membrane takes place by activation of MMP-9. 8 The MMP-9 À1562C4T polymorphism is a promoter polymorphism and the T-allele enhances the expression of the MMP-9 messenger RNA in cells.…”
Section: Mmp-9 Gene and Arterial Stiffness In Hypertension S Zhou Et Almentioning
confidence: 99%
“…Associations between collagen synthesis and degradation and arterial stiffness have been demonstrated in normotensive and hypertensive individuals (McNulty et al 2006) , and patients with dilated cardiomyopathy (Bonapace et al 2006). However, this is a relatively new area of research, and further work is needed to delineate the relationship between collagen turnover and arterial stiffness.…”
Section: Arterial Stiffnessmentioning
confidence: 99%